Correlation between epithelial cell proliferation and histological grading in gastric mucosa. Issue 5 (1st May 1999) - Lynch, D A; Mapstone, N P; Clarke, A M; Jackson, P; Moayyedi, P; Dixon, M F; Quirke, P; Axon, A T
Abstract : AIM: To determine if there is a correlation between the histological findings in the gastric mucosa and the degree of cell proliferation in gastric antral biopsies. METHODS: Cell proliferation in gastric antral biopsies was determined by in vitro bromodeoxyuridine labelling. Histological sections were assessed using the Sydney System. RESULTS: There was a positive correlation between antral mucosal cell proliferation and the acute inflammatory cell infiltrate (r = 0.29; p = 0.03). There was a stronger correlation with the chronic inflammatory cell infiltrate (r = 0.53; p < 0.0001) and the density of H pylori colonisation (r = 0.54; p < 0.0001). There was no correlation between gastric epithelial proliferation and the degree of atrophy. Stepwise multiple regression indicates that the only independent predictor of epithelial cell proliferation is the density of H pylori colonisation (p < 0.0001). CONCLUSIONS: H pylori increases gastric epithelial cell proliferation through the mucosal inflammatory response and probably by other means. The strong correlation between epithelial proliferation, the chronic inflammatory cell infiltrate, and the density of H pylori colonization may have implications for gastric carcinogenesis.